2022
DOI: 10.1128/jvi.00469-22
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Porcine Epidemic Diarrhea Virus nsp1 Cause Increased Viral Sensitivity to Host Interferon Responses and Attenuation In Vivo

Abstract: PEDV causes porcine epidemic diarrhea (PED) and remains a great threat to the swine industry worldwide because no effective vaccines are available yet. Safe and effective live attenuated vaccines can be designed using reverse genetics to induce lactogenic immunity in pregnant sows to protect piglets from the deadly PED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…In addition to structure proteins, nonstructural proteins, including nsp1, nsp15, and nsp16, are also linked to the virulence of PEDV. Niu et al mutated two amino acids (N93A and N95A) in PEDV nsp1 and noted that the recombinant virus increased viral sensitivity to the host immune response and demonstrated an attenuation phenotype in vivo [52]. We also found that complement component 3 (C3) significantly inhibited PEDV replication in vitro; however, PEDV can antagonize the immune suppression of C3 via inhibition of the nsp1 phosphorylation of CEBP/β [59].…”
Section: Virulence Determinant Identificationmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition to structure proteins, nonstructural proteins, including nsp1, nsp15, and nsp16, are also linked to the virulence of PEDV. Niu et al mutated two amino acids (N93A and N95A) in PEDV nsp1 and noted that the recombinant virus increased viral sensitivity to the host immune response and demonstrated an attenuation phenotype in vivo [52]. We also found that complement component 3 (C3) significantly inhibited PEDV replication in vitro; however, PEDV can antagonize the immune suppression of C3 via inhibition of the nsp1 phosphorylation of CEBP/β [59].…”
Section: Virulence Determinant Identificationmentioning
confidence: 64%
“…Identification of the virulence factors in CoVs is essential for the rational design of live-attenuated vaccine candidates. To date, an extensive effort has been made toward understanding the virulence factors of the emerging and re-emerging swine CoVs [48][49][50][51][52][53][54][55]. Many studies have suggested that the virulence of PEDV is associated with its S protein.…”
Section: Virulence Determinant Identificationmentioning
confidence: 99%
“…Multiple proteins of PEDV have been shown to inhibit IFN responses during infection (214)(215)(216)(217)(218)(219). The nsp1 protein of PEDV is the most potent viral IFN antagonist (214), and three residues of F44, N93, and N95 of nsp1 are critical for both type I and type III IFN suppression (52,220). PEDV nsp1 suppressed both types of IFN responses by interrupting the IRF3 and CREB-binding protein association and suppressing transcription factors (52) (Figure 1).…”
Section: Porcine Epidemic Diarrhea Virusmentioning
confidence: 99%
“…A replication-competent PEDV mutant with an IFN inactive version of nsp1 induced IFN response in IFN-responsive cells ( 52 ). It was further demonstrated that PEDV carrying the nsp1 N93/95A mutation triggered a significantly higher level of IFN response and induced 100% protection from severe diarrhea and death in neonatal piglets post-challenge ( 220 ). These findings suggest that nsp1 is an essential virulence determinant for CoVs, providing a potential paradigm for the development of a new vaccine based on IFN modification.…”
Section: Reprograming Viral Immune Evasion and Experimental Infection...mentioning
confidence: 99%
“…It targets host translation machinery and the interferon (IFN) response system to induce host mRNA degradation and antagonize IFN responses [45][46][47][48]. The replication-transcription complex (RTC), responsible for viral RNA synthesis, consists of multiple viral nonstructural proteins [49][50][51]. Among the proteins involved in the RTC, nsp3-nsp6 are responsible for modulating intracellular membranes and assembling double-membrane vesicles (DMV), where viral RNA synthesis occurs [52,53].…”
Section: Pedv Replication and Functional Elements In Transcriptionmentioning
confidence: 99%